Apoptosis induced by a GnRH analogue in a granulosa cell line from bovine ovary (BGC-1) - Cruzans, P.R. (2012)
Gonadotrophin releasing hormone receptors (GnRHR) have been identified in ovarian granulosa cells (GC) and luteal cells (CL). It has also been observed that the activation of GnRHR in GC regulates gonadal function. Studies using GnRH agonists (GnRHa) in rat ovaries, in vivo and in vitro, showed an increase in follicular atresia. Our objective was to study the regulation of apoptosis inan established line of bovine granulosa cells (BGC-1) usin gleuprolide acetate (LA) as GnRHa and ANTIDE as competitive antagonist. \nOur results demonstrate a significant increase in the proportion of apoptotic cells induced for 24 and 48 hs with 100 nM LA by morphological techniques (DAPI staining and Hematoxilin), membrane markers expression (Annexin V-FITC and PI detected by flow cytometry) and biochemical techniques such as determining caspase 3 activity. Apoptosis was partially inhibited by ANTIDE, showing per se activity when caspasa 3 activity was evaluated.\nThe analysis of the intracellular pathways regulating the apoptotic process revealed the existence of a mechanism that involves the activation of the intrinsic pathway, throughthe analysis of protein expression of Bcl-2 family (Bax and Bcl-2) andtheinhibition of the extrinsic pathway by inhibiting the activity of the enzyme phospholipase D (PLD). It is proposed that ANTIDE works as antagonist of the intrinsic pathway but as extrinsic pathway agonist as inhibiting the activity of PLD.